What do we know about the “September events” in 1991 in Uralsk? (Journal of history, 2021)
This year, special attention is paid to the upcoming 30-th anniversary of the independence of our country. The country’s future and its independence are closely related concepts. For history, thirty years are like a moment flashing in one impulse.Since 1991, the first pages of Independent Kazakhstan have been launched. There is an urgent need to explain to the younger generation all the milestones of this difficult path, the path of downtime, the path of searches. We present to the readers’ attention the situation during «September events» in Uralsk, coinciding in time with the period of gaining independence, but undeservedly forgotten. Opinions are possible that they relate only to the history of the region, and should not have any relation to the gen- eral history. It should be noted that the integral history of the country is made up of the histories of the regions. This event was one of the first tests of independent Kazakhstan, a challenge to our territorial integrity.The vast majority of the population of the region gave their assessment of what happened then. The President of the country also gave him his fair assessment N. Nazarbayev.Our future generation should live in peace in harmony with all the people of Kazakhstan, as well as with its neighbor Russia.Key words: Independence, September events in Uralsk, “Cossacks’ holiday”, M.I. Yessenaliev and Azat representatives, “Society of Kazakhs” and “Revival committee”, rally, campaign work, conversion of defense enterprises.